Investigating Trends in Discharge Destinations and Impact on Allied Health Service Utilization in an Australian Hospice. (September 2014) - Yoong, Jaclyn; Boughey, Mark; Leung, Sarah
Australia's population is aging and increasing. The palliative care needs of the population are also increasing in parallel, with more patients being referred to services for a broad range of reasons including symptom management, psychosocial support, and end-of-life care. Our study looks at how this manifests at on inpatient hospice in Melbourne, Australia, in terms of discharge destinations and allied health service utilization. We noted a trend in more discharges to residential care facilities, which appeared more likely for those patients who were admitted for assessment or had longer length of stay. Patients who were admitted for assessment also appeared in overall to utilize allied health services more than those admitted for end-of-life care. This information will help tailor resource allocation according to the current trends.